1996
DOI: 10.1007/bf01799110
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial encephalomyopathies: what next?

Abstract: In few areas of medicine has progress been more spectacular than in the field of mitochondrial diseases, especially those related to mtDNA mutations. Much remains to be done, however, and this brief review discusses the following areas of research where progress has been more limited or data are still controversial: (1) the molecular basis of respiratory-chain defects due to nuclear DNA mutations; (2) defects of mitochondrial protein importation; (3) defects of intergenomic signalling; (4) pathophysiology of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 64 publications
1
40
0
1
Order By: Relevance
“…We are following up unaffected mutated relatives. If the cardiomyopathy phenotype indeed is related to the amount of mutated mtDNA in the affected organ as in encephalomyopathies, 13 clinical follow-up of mutated but healthy relatives should allow early detection of disease. A recent study done in 58 unrelated patients with DCM showed that mtDNA point mutations are significantly more frequent in patients than in controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are following up unaffected mutated relatives. If the cardiomyopathy phenotype indeed is related to the amount of mutated mtDNA in the affected organ as in encephalomyopathies, 13 clinical follow-up of mutated but healthy relatives should allow early detection of disease. A recent study done in 58 unrelated patients with DCM showed that mtDNA point mutations are significantly more frequent in patients than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Activity of complex II is not affected as it is entirely encoded by nuclear DNA, whereas cytochrome C oxidase (Cox) activity (or complex IV), which is partially encoded by mtDNA genes and constitutes the electron transport chain along with complex I, 12 is frequently reduced in patients with mtDNA tRNA mutations. Pathological tRNA mutations are characteristically heteroplasmic and absent from controls and affect highly conserved regions; 12,13 tRNA mutations have been reported in patients with hypertrophic cardiomyopathy, particularly in those who develop late congestive heart failure 14 or with not otherwise defined cardiomyopathies and congestive heart failure. 5,6,9 Rarely, missense mutations in polypeptide-coding genes have been linked to multisystem syndromes.…”
mentioning
confidence: 99%
“…We believe that much of the clinical and biochemical heterogeneity can be explained by the rules of mitochondrial genetics and attributed to various factors (DiMauro, 1996).…”
Section: Defects Of Mitochondrial Genesmentioning
confidence: 93%
“…Since then, the field of mitochondrial disorders has become a focus not only within neurology but also of various other disciplines (Moraes, 1996;Ozawa, 1997). In few areas of medicine has progress been more spectacular (DiMauro, 1996). Primary defects in mitochondrial function are now implicated in over 100 diseases, and the list continues to grow (Luft, 1994).…”
Section: Introductionmentioning
confidence: 97%